Patterns of Islamic Education in Child Care Services in Kejapanan Village, Gempol District, Pasuruan Regency - Mardhiana Amalia Dessy Fadzrina Ilham; Budi Hariyanto (Universitas Muhammadiyah Sidoarjo, 2021)
This research is a descriptive research type, and the type of approach used is qualitative. In the book by Sukmadinata, it explains that